The Analysis of the Role of Electronic Word of Mouth (E-WOM) in Increasing the Number of Customers at Bank Sumut Syariah KCP Rantauprapat - Mei Linda Ritonga; Yenni Samri Juliati Nasution; Muhammad Ikhsan Harahap (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
The increasingly competitive development of the business world means that Bank Sumut Syariah must make efforts to carry out promotions to introduce its products to the public in an effective way. One strategy to increase the number of customers is to utilize Electronic Word of Mouth (E-WOM) which is considered an effective promotional strategy to increase the number of customers. The aim of this research is to find out the role of Electronic Word of Mouth (E-WOM) in increasing the number of customers at Bank Sumut Syariah KCP Rantauprapat. The research method used in this research is a descriptive-qualitative method with literature study and the types of data used are primary and secondary data. Primary data acquisition was carried out using the interview method and secondary data in the form of supporting documents and previous research relevant to this research. The results obtained from this research are that the E-WOM indicator plays a very important role in attracting customers' interest in using Bank Sumut Syariah KCP Rantauprapat products. What plays the most role in attracting customer interest is the content indicator where customers obtain information and education from content published through the company's social media. E-WOM Bank Sumut Syariah was formed from comments submitted by customers on the Bank Sumut Syariah KCP Rantauprapat website which can be accessed by anyone who wants to get further information about Bank Sumut Syariah KCP Rantauprapat.